Diversity of spiders in Fanjing Mountain Nature Reserve, Guizhou, China, III: A new species of Brommella (Dictynidae) - Lu, Tian; Chen, Hui-Ming; Zhang, Zhi-Sheng (Zootaxa, 2015)
A new Chinese species of the dictynid genus Brommella Tullgren—Brommella digitata sp. nov.—from Fanjing Mountain Nature Reserve of Guizhou Province is photographed, illustrated and described. It can be distinguished from other Brommella species by the complex conductor and finger-like tegular apophysis of the male palp and anteriorly located copulatory openings of the female epigyne. This is the second species of Brommella from China. Additional photos, illustrations and material of B. punctosparsa (Oi 1957) are provided for comparison. The serrated embolus is firstly described for both species on the basis of SEM photos.